Pelatihan, Iklim Kerja, dan Kompetensi Terhadap Kinerja Guru di Madrasah Tsanawiyah Negeri 1 Batang Hari - Etty Siswati; Niki Kosasi; Evi Fauzani; Elsi Putri Anjelina (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The aim of this research is to explain the influence of training , work climate and competency on teacher performance at Madrasah Tsanawiyah (MTs) Negeri 1 Batang Hari.Quantitative analysis method the use multiple linear regression analysis tools. Testing of training variables, work climete and competency teacher performance as the dependent variable, was carried out using the t-test and F-test. The results of the partial research (t-test) show that the training t-value is 2.237 > from the t-table number 1.649, this it can be seen that training influences teacher performance. The work climate t-value is 4.126 > the t-table number 1.649 with the work climate having an effectnon teacher performance. The competency t-value is 3.048 > from the table namber 1.649, so can be seen the compentency has an influence on teacher performance. Training ,work climate and competence silmultanseously (F tast) obtained F-count 18.523 > F-table of 2.90, meaning that training, work climate and competence have a positive effest simultaneously or together onteacher performance at MTs Negeri 1 Batang Hari. The resulting adjusted R square was 0.683. So it can be concluded that the percantage of training work climate and competency variables on teacher performance at MTs Negeri 1 Batang hari is 68,3 %.